A power supply clamp with self-cutoff the conducted ESD current path mechanism for latch-up free. (December 2022) - Sun, Kangming; Meng, Liya; Xia, Yang
Highlights: A power supply clamp with self-shutdown mechanism for on-chip ESD (electrostatic discharge) protection is developed by TCAD simulation and experiments. The proposed structure can automatically set block to cut off the conducted SCR by ESD stress. By properly sequencing turn-off signal, the reported structure presents automatic self-shutdown capability and latch-up free characteristic even under power-on case. Abstract: A power supply clamp with self-cutoff the conducted ESD (electrostatic discharge) current path mechanism for on-chip ESD protection is developed by TCAD simulation and experiments. The proposed clamp consists of SCR (silicon controlled rectifier) acting as ESD protection device between power and ground rail, and control circuit generating cutoff signal. Different from the traditional SCR which increases holding voltage to prevent latch-up, the proposed structure can automatically set block to cut off the conducted SCR after triggered by ESD stress. Simulation analysis and experimental results show that the reported structure presents self-cutoff capability and latch-up free characteristic even under power-on case.